2015
DOI: 10.1073/pnas.1506377112
|View full text |Cite
|
Sign up to set email alerts
|

Subset of early radial glial progenitors that contribute to the development of callosal neurons is absent from avian brain

Abstract: The classical view of mammalian cortical development suggests that pyramidal neurons are generated in a temporal sequence, with all radial glial cells (RGCs) contributing to both lower and upper neocortical layers. A recent opposing proposal suggests there is a subgroup of fate-restricted RGCs in the early neocortex, which generates only upper-layer neurons. Little is known about the existence of fate restriction of homologous progenitors in other vertebrate species. We investigated the lineage of selected Emx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 68 publications
(98 reference statements)
3
45
0
Order By: Relevance
“…Slides were blocked with subsequent incubations in 1 mg/mL sodium borohydride and 5% goat serum in PBS with 0.25% Triton X-100/0.1% BSA. Slides were incubated with 1:500 dilution of anti-NeuN antibody (MAB377, EMD Millipore 55 ) overnight at 4 °C, washed with PBS/0.1% BSA/0.1% Triton X-100, and incubated 90 min at room temperature (20–25 °C) with Oregon Green 488 anti-mouse antibody (Life Technologies). Slides were subsequently incubated with 1 ug/mL DAPI for 10 min to visualize nuclei, and autofluorescence was blocked by incubation with 0.1% Sudan Black in 70% ethanol.…”
Section: Methodsmentioning
confidence: 99%
“…Slides were blocked with subsequent incubations in 1 mg/mL sodium borohydride and 5% goat serum in PBS with 0.25% Triton X-100/0.1% BSA. Slides were incubated with 1:500 dilution of anti-NeuN antibody (MAB377, EMD Millipore 55 ) overnight at 4 °C, washed with PBS/0.1% BSA/0.1% Triton X-100, and incubated 90 min at room temperature (20–25 °C) with Oregon Green 488 anti-mouse antibody (Life Technologies). Slides were subsequently incubated with 1 ug/mL DAPI for 10 min to visualize nuclei, and autofluorescence was blocked by incubation with 0.1% Sudan Black in 70% ethanol.…”
Section: Methodsmentioning
confidence: 99%
“…apes and primates) (Otani et al, 2016). As the field of comparative cell biology of neocortical neurogenesis recently experienced a renaissance (Fietz et al, 2010, García-Moreno and Molnár, 2015, García-Moreno et al, 2012, Kelava et al, 2012, Lewitus et al, 2014, Reillo et al, 2011), we are sure that the development of protocols for different mammalian species will deepen our insight into evolutionary aspects of neurogenesis.…”
Section: Brain Organoids Of the Futurementioning
confidence: 99%
“…More precisely, we have suggested that Pax6 upregulation, among other genes, has been critical for brain expansion in all amniotes and possibly all vertebrates, and differences in brain morphology may partly relate to differential spatiotemporal regulation of Pax6 in the different lineages (Aboitiz & Montiel, 2007Montiel & Aboitiz, 2015, 2018. In this line, recent findings indicate that the superficial layers of the mammalian neocortex are produced by a late population of Pax6-dependent progenitors that is not present in birds (García-Moreno & Molnár, 2015;Yamashita et al, 2018). Furthermore, we have proposed that upregulation of additional morphogens produced in the embryonic dorsomedial hemisphere (the so-called cortical hem) and overexpression of the reelin protein may have specifically contributed to the expansion of the dorsal pallium and the emergence of the laminated mammalian neocortex (Montiel & Aboitiz, 2015, 2018.…”
Section: Indirect Neurogenesismentioning
confidence: 85%